Determinants of chestnuts demanded quantities: an empirical estimation using panel data - Mourão, Paulo (2007)
In this work, we studied the economic determinants of chestnuts demanded quantities. It concludes by stating that chestnuts are only demanded in countries with the tradition of their presence in people’s diets, receiving strong challenges from the globalisation process. We also have found a significant dependence on real income per capita of chestnuts demanded quantities. Price effects were concluded as not influencing CDQ in the panel estimations.